2019
DOI: 10.1108/itse-01-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between a computer-based and a mobile-based assessment

Abstract: Purpose The purpose of this study is to compare the overall usability and user experience of desktop computers and mobile-devices when used in a summative assessment in the context of a higher education course. Design/methodology/approach The study follows a between-groups design. The participants were 110 first-year undergraduate students from a European university. Students in the experimental group participated in the assessment using mobile devices, whereas students in the control group participated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A seven-week online discussion experiment showed that smartphone use outperforms computer use in learning preparation, learning motivation, learner-interface interaction and flow experience (Kyung, 2015). A recent study found that smartphone users report higher attractiveness and novelty than computer users when engaging in summative assessments (Nikou and Economides, 2019). Therefore, this study proposes the following hypothesis:…”
Section: Factors Influencing Teenagers' Digital Reading Flow Experiencementioning
confidence: 89%
“…A seven-week online discussion experiment showed that smartphone use outperforms computer use in learning preparation, learning motivation, learner-interface interaction and flow experience (Kyung, 2015). A recent study found that smartphone users report higher attractiveness and novelty than computer users when engaging in summative assessments (Nikou and Economides, 2019). Therefore, this study proposes the following hypothesis:…”
Section: Factors Influencing Teenagers' Digital Reading Flow Experiencementioning
confidence: 89%
“…The first was a Likert-scale questionnaire to survey the participants' views of the workshops. The questionnaire was based on the work of Nikou & Economides (2019). However, quantitative methods can give us a clear understanding of the findings and the reason behind them, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…This includes the user's physical, cognitive, and emotional experience. The factors that are considered in measuring this experience vary in the literature and identifying these factors is an ongoing process in various studies (International Organization for Standardization, 2018; Moczarny et al, 2012;Nikou & Economides, 2019;Rhiu et al, 2020;Rogers et al, 2002). However, certain design aspects, like authenticity, immersion, and instructional support, that influenced the virtual learner experience (VLX) while using the VRLE have not been considered as part of UX in the current literature, and do not form part of the UX of general computer systems.…”
Section: Extending Ux To Form Vlxmentioning
confidence: 99%